Variability of Alternaria brassicicola Causing Leaf Blight of Cabbage in Major Cabbage Growing Districts of Assam, India - Hazowary, Jangila; Upamanya, Gunadhya Kumar; Kashyap, Anurag (International Journal of Bio-resource and Stress Management, 2023)
The research was conducted at Assam Agricultural University, Jorhat, Assam, India during September, 2021–May, 2022 to study the variation of Alternaria brassiciola infecting cabbage. Fifteen isolates of Alternaria brassicicola which infected cabbage were collected from six different districts in Assam and their variability was investigated. Within the in vitro setting, it was observed that all isolates exhibited significant variation in terms of conidial length, breadth, and septal count. The isolates displayed a range of average conidial length and breadth spanning from 20.45µm to 29.74µm and 6.56µm to 9.89µm, respectively. Additionally, the isolates exhibited a variation in transverse septa with counts ranging from 4 to 6 and longitudinal septa, ranging from 0.13 to 0.41. Regarding the colony colour, four distinct variations, ranging from dark grey-green to dark brown-green and from mild olive green to greyish olive green were observed. These colonies featured edges in shades of white, greyish, brownish, or green edges and their shapes varied between round and irregular, accompanied by either a fluffy or compressed growth pattern. The diameter of the radial growth, observed on the fifteenth day after inoculation, varied from 57.3 mm to 84.2 mm. In RAPD analysis it was evident that the Jorhat isolates (AbJor_2) and the Barpeta isolate, (AbBa_1) exhibited the highest genetic similarity, as indicated by the lowest genetic distance with the coefficient of similarity 0.484. Conversely, the Jorhat isolates (AbJor_3) and Barpeta isolate (AbBa_1) shared the least genetic similarity, with the coefficient of similarity 0.021.